The 'new' Manley and the new political economy of Jamaica - Payne, Anthony (1992)
Discusses Manley's new approach to government after the 1989 elections, with special emphasis on the management of the Jamaican political economy during the 3 years the 'new' Manley government was in office. Argues that the approach developed over time and under pressure, with Manley and his government was forced by events rather than charting a new course.